1980
DOI: 10.1073/pnas.77.12.7473
|View full text |Cite
|
Sign up to set email alerts
|

Release of enkephalins and enkephalin-containing polypeptides from perfused beef adrenal glands.

Abstract: Enkephalins and enkephalin-containing polypeptides were released from perfused bovine adrenal glands bynicotine and Ba2+, agents that release catecholamines. All the enkephalin-containing polypeptides that are normally found in the a renal medulla were released by the two secretagogues in approximately the same proportions as are present in adrenal chromaffin granules.It has long been thought that the function of the adrenal medulla is to secrete catecholamines, mainly epinephrine, in response to stressful sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Thus, we focused on the source of endogenous opioids. The adrenal gland is known to synthesize and release opioid peptides including β‐endorphin . Therefore, we employed bilateral adrenalectomy to verify the source of the increased plasma BER observed in STZ‐diabetic rats induced by diosmin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we focused on the source of endogenous opioids. The adrenal gland is known to synthesize and release opioid peptides including β‐endorphin . Therefore, we employed bilateral adrenalectomy to verify the source of the increased plasma BER observed in STZ‐diabetic rats induced by diosmin.…”
Section: Discussionmentioning
confidence: 99%
“…The enkephalin-containing polypeptides (ECPs) found in the adrenal medullary chromaffin cells have been shown to be secreted in response to the same stimuli that induce epinephrine release (8)(9)(10). Since exercise stimulates catecholamine release, specifically epinephrine (11)(12)(13), it was hypothesized that the ECPs would also respond to exercise stress.…”
mentioning
confidence: 99%
“…Previous studies and the present work have shown that sequential enzymatic digestion of the peptides of the adrenal gland generates up to 80-90 % ofthe total (met)enkephalin immunoreactivity. It has already been found (Kilpatrick et al 1980;Rossier et al 1981) that the large enkephalincontaining peptides are released together with catecholamines in response to physiological stimuli. The results given in the present paper indicate that such an assumption may be erroneous since we have found that, in response to electrical stimulation of the splanchnic nerves, one-half of the total (met)enkephalin immunoreactivity released comprises free (met)enkephalin, (met)enkephalyl-arg-phe and (met)enkephalyl-arg-gly-leu.…”
Section: Characterization Of the Released Enkephalin-like Materialsmentioning
confidence: 99%
“…Several studies have indicated that enkephalin immunoreactive products or opioid peptide-like products are co-released with catecholamines from the adrenal medulla in vitro (Kilpatrick, Lewis, Stein & Udenfriend, 1980;Stine, Yang & Costa, 1980;Livett, Dean, Whelan, Udenfriend & Rossier, 1981; Udenfriend, 1981; Corder, Mason, Perrett, Lowry, Clement-Jones, Linton, Besser & Rees, 1982) and in vivo (Hexum, Hanbauer, Govoni, Yang & Costa, 1980; Govoni, Hanbauer, Hexum, Yang, Kelly & Costa, 1981). Furthermore, it was recently shown (Livett, Day, Elde & Howe, 1982;Pelto-Huikko, Salminen & Hernoven, 1982) that in the adrenal medulla, enkephalin immunoreactivity is present in adrenergic chromaffin cells but not in noradrenergic cells.…”
Section: Introductionmentioning
confidence: 99%